Numerical studies of surface potential, mobility and Seebeck coefficient of organic thin film transistor based on 2,3 benzanthracene: Light effect - Jouili, A.; Mansouri, S.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; El Mir, L.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2017)
The white light illumination effect has a large influence on charge carrier transport in organic thin-film transistors (OTFTs). In this work, an analytical model is presented for OIFIs using the variable range hopping (VRH) theory to discuss the Gaussian DOS distribution, the surface potential, the mobility and the Seebeck coefficient of the 2,3 benzanthracene thin-film transistor under dark and white light illuminations. This model explains the influence of illumination on the carrier density, the Gaussian DOS distribution effectively on the surface potential and the Seebeck coefficient. The White light illumination effect can remarkably enhance the surface potential at high gate voltages, as well as reduce the energetic disorder dependence of the Seebeck coefficient. Finally, according to the variable range hopping (VRH) model an analytical model has been also developed to simulate the transfer characteristics of organic phototransistor based on 2,3 benzanthracene and the obtained theoretical results show an excellent agreement with the experimental data.
Keywords: Benzanthracene-TFT; Surface potential; Seebeck coefficient; DOS - TFT; Mobility; Light effect